Association between insight and outcome of psychotherapy: systematic review and meta-analysis - Jennissen, Simone; Huber, Julia; Ehrenthal, Johannes C.; Schauenburg, Henning; Dinger, Ulrike (The American journal of psychiatry, 2018)
Objective:An increased understanding of repetitive dysfunctional patterns and their relationship to an individual’s life history is regarded as a key mechanism of change in insight-oriented therapies. At the same time, empirical research on the insight-outcome relationship is rare, and its generalizability is restricted by the use of a wide range of definitions and methods among studies. The authors conducted a meta-analysis to systematically examine the association between patient insight and psychotherapy outcome across a range of treatment modalities.Method:Insight was defined as patients’ understanding of associations between past and present experiences, typical relationship patterns, and the relation between interpersonal challenges, emotional experience, and psychological symptoms. From 13,849 initially identified abstracts, the authors extracted 23 independent effect sizes. A random-effects meta-analysis was performed to assess the magnitude of the insight-outcome relationship. Risk of publication bias was assessed with funnel plot inspections, Egger’s regression test, and Duval and Tweedie’s trim-and-fill procedure as sensitivity analyses.Results:A significant, moderate correlation (r=0.31) was observed between insight and treatment outcome. Sensitivity analyses demonstrated the robustness of the results.Conclusions:The findings support the importance of insight for psychotherapy outcome. Insight may be a relevant mechanism of change across different treatment modalities.
Gesehen am 03.03.2020